2022
DOI: 10.1515/sjpain-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying workers on sick leave due to musculoskeletal pain: translation, cross-cultural adaptation and construct validity of the Norwegian Keele STarT MSK tool

Abstract: Objectives Stratified care using prognostic models to estimate the risk profiles of patients has been increasing. A refined version of the popular STarT Back tool, the Keele STarT MSK tool, is a newly developed model for matched treatment across a wide range of musculoskeletal pain presentations. The aim of this study was to translate and culturally adapt the Keele STarT MSK tool into Norwegian, examine its construct validity and assess the representativeness of the included sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…This approach has been supported by a recent umbrella review indicating that there are a number of common prognostic factors among patients with MSK-complaints including: worse baseline function, higher symptom/pain severity, worse mental well-being, more comorbidities, older age and higher body mass index [16]. Several translations of the STarT-MSK-Tool are available, but a German version did not exist and knowledge about its measurement properties is limited [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been supported by a recent umbrella review indicating that there are a number of common prognostic factors among patients with MSK-complaints including: worse baseline function, higher symptom/pain severity, worse mental well-being, more comorbidities, older age and higher body mass index [16]. Several translations of the STarT-MSK-Tool are available, but a German version did not exist and knowledge about its measurement properties is limited [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was a low volume of missing data for the prognostic factor variables and no missing data on variables used to calculate the outcome scores. Finally, the risk of selection bias is assumed to be low, as previous research 62 broadly confirms representativeness of the study sample.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the study sample is largely representative of the population of workers on sick leave due to MSDs in terms of the distribution of socio-demographic variables (age, gender, musculoskeletal diagnosis, occupational group, annual salary, and geographical location) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%